Attempts of Forcing Oil Production on the Eve of the Great Patriotic War - Bodrova, Elena V.; Kalinov, Vyacheslav V.; Krasivskaya, Valeria N. (International Journal of Criminology and Sociology, 2022)
In this study, the problem of attempts to reorganize the USSR's oil industry on the eve of the Great Patriotic War and speed up oil production and oil refining to ensure industrialization and defense plans are investigated. The conclusion is formulated that the plans were not fully supported by financial, human, and technological resources. The reasons for the failure to fulfill the plans were strategic miscalculations, ignoring the recommendations of leading scientists and the repression against a significant number of brilliant oil specialists who restored industry in the 1920s, reconstructing it and ensuring the flow of currency through the expansion of oil exports. The measures taken on the eve of the war to reorganize the management of the oil industry, its technical re-equipment, and intensification of oil production yielded specific results. But the growth rate of production was also hindered by insufficient exploration of areas and their unpreparedness for exploitation. Before the war, Azerbaijan remained the main oil base of the USSR. The development of “Second Baku” was unacceptably slow.